The Civilising Offensive. Social and educational reform in 19th century Belgium - de Spiegeleer, Christoph (New Perspectives on the History of Liberalism and Freethought, 2019)
Around 1850 Belgium was continental Europe`s most heavily industrialised state. From the mid-century until the Belle Époque many international social reform associations were based in Belgium. This book will stimulate the debate between historians & social pedagogues on the 19th-century bourgeois ´civilising offensive` and place the history of social, moral and educational reform in Belgium within a broader European perspective.